Analyzing cognitive biases impacting investor decision-making in Urban investment projects - Rouhollah Shahnazi; Mojtaba Panahi (اقتصاد شهری)
Investment attraction and fostering investor engagement represent critical focal points for national and local governments. In recent years, interdisciplinary fields such as behavioral economics have explored novel approaches to understanding investment attraction and its associated challenges. Traditional economic analyses often fail to capture the complexities of investor decision-making due to methodological limitations and unrealistic assumptions. Behavioral economics research illuminates the presence of cognitive biases that individuals exhibit when entering investment projects, many of which are predictable. These findings present fresh opportunities for gaining deeper insights into investor behavior and optimizing policies related to investment attraction. Accordingly, this study aims to identify behavioral factors and cognitive biases influencing urban investment attraction, offering valuable insights for municipal planners nationwide. The study adopts an applied research design, utilizing a survey methodology. The targeted population in 2023, includes employees of municipal investment organizations, professionals in investment-related sectors, researchers specializing in investment studies, and experienced investors. The sample size was determined based on Morgan's table, with 105 participants selected through random sampling. The research findings highlight that cognitive biases, namely overconfidence, framing effect, loss aversion, optimism, regret aversion, and halo effect, exert the most substantial influence on investors' choices and decision-making processes. By delving into behavioral economics, this study contributes to a deeper understanding of the cognitive biases that shape investor behavior in urban investment projects. The implications derived from these findings hold immense value for municipal planners, enabling them to devise more effective strategies to attract investors and optimize investment policies.